The Logic of the Body : Retrieving Theological Psychology - LaPine, Matthew A. (Bellingham, WA : Lexham press, 2020)
"When it comes to stress and worry, that's all we really need to say, right? Just repent of your anxiety, and everything will be fine. But emotional life is more complex than this. In The Logic of the Body, Matthew A. LaPine argues that Protestants must retrieve theological psychology in order to properly understand the emotional life of the human person. With classical and modern resources in tow, LaPine argues that one must not choose between viewing emotions exclusively as either cognitive and volitional on the one hand, or simply a feeling of bodily change on the other. The two "stories" can be reconciled through a robustly theological analysis. In a culture filled with worry and anxiety, The Logic of the Body offers a fresh path within the Reformed tradition."--
Foreword -- Preface -- Abbreviations -- Introduction -- Problem -- Theological psychology: a path foreword -- Governing assumption and thesis -- Methodology and approach -- Chapter overview -- Literature overview -- Excursus: passions and affections -- 1. Emotional voluntarism -- The explanation dilemma -- The treatment dilemma -- Recovery project -- 2. The psychology of Thomas Aquinas -- The hylomorphic powers of the soul -- Aquinas's physiology -- Acts and passions -- Habit and virtue -- Conclusion -- 3. Developments in medieval and renaissance psychology -- The nature of the soul -- The functions of the soul: the ascendency of the will in action theory -- Conclusion -- 4. The psychology of John Calvin -- Calvin's sources -- The soul, the body, and the Imago Dei -- The neglected body -- Substance and immortality of the soul -- Faculties Calvin on the will -- Affections, passions, and virtue -- Virtue and vice -- Historical postscript -- 5. Modern reformed psychology -- Reformed theological context -- Embedded psychological assumptions -- Reformed formulations of body and soul -- Evaluation -- 6. Book of nature: body and soul -- The state of the soul in review -- Theological and philosophical arguments for dualism -- Theological and philosophical arguments for Monism -- Thomistic dualism -- 7. Book of scripture: the body in biblical theology -- Biblical theological reflections on human agency -- 8. Book of nature: embodied emotion -- Setting the stage: emotion and cognition -- LeDoux's new model -- A model -- The subjective logic -- 9. Books of scripture: commanding emotion -- Elliott's psychological assumptions -- An alternate reading of Matthew 6:25-34 -- Conclusion -- Conclusion -- Revisiting Mary -- Six theses on therapy and embodiment -- Appendix: On the heart -- Bibliography -- Subject/Author index -- Scripture index.
Includes bibliographical references (pages 365-403) and index.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Calvin, Jean, -- 1509-1564.; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Calvin, Jean, -- 1509-1564.; Theological anthropology -- Christianity; Psychology, Religious -- Theology; Emotions -- Religious aspects -- Christianity; Mental health -- Religious aspects -- Christianity; Christianity -- Psychology; Psychology and religion; Psychology and religion; Mental health -- Religious aspects -- Christianity; Emotions -- Religious aspects -- Christianity; Theological anthropology -- Christianity; Christianity -- Psychology